2015
DOI: 10.1242/jcs.168179
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial MMP14 is required for endothelial dependent growth support of human airway basal cells

Abstract: Human airway basal cells are the stem (or progenitor) population of the airway epithelium, and play a central role in anchoring the epithelium to the basement membrane. The anatomic position of basal cells allows for potential paracrine signaling between them and the underlying nonepithelial stromal cells. In support of this, we have previously demonstrated that endothelial cells support growth of basal cells during co-culture through vascular endothelial growth factor A (VEGFA)-mediated signaling. Building on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…BM ECs regulate HSC fate, in part, via the elaboration of paracrine factors . Commensurate with these observations, recent studies have suggested that ECs also regulate the self‐renewal and regeneration of stem cells in nonhematopoietic organs, including the liver, brain, lung, and skin , . In the present study, we describe the hematopoietic‐specific activities of BM ECs and highlight the potential for EC‐derived paracrine mechanisms to be translated into regenerative therapies for patients.…”
Section: Introductionsupporting
confidence: 65%
“…BM ECs regulate HSC fate, in part, via the elaboration of paracrine factors . Commensurate with these observations, recent studies have suggested that ECs also regulate the self‐renewal and regeneration of stem cells in nonhematopoietic organs, including the liver, brain, lung, and skin , . In the present study, we describe the hematopoietic‐specific activities of BM ECs and highlight the potential for EC‐derived paracrine mechanisms to be translated into regenerative therapies for patients.…”
Section: Introductionsupporting
confidence: 65%
“…The progenitors of airway basal cells 91 could also proliferate in response to angiocrine MMP-14 induction. FGF-2 and FGF-5 derived from cultured human basal cells stimulate the FGFR-1-dependent production of MMP-14 by pulmonary capillary ECs, which in turn supports the expansion and differentiation of basal cells 92 . Therefore, selective angiocrine upregulation of MMP-14 in pulmonary capillary ECs ignites the propagation of alveolar epithelial cells and basal cell progenitors.…”
Section: Regeneration Of the Lung Epitheliummentioning
confidence: 93%
“…Among these, MMP14 is a membrane-type MMP (MT-MMP) belonging to the collagenase type I class. In the vascular setting, MMP14 is involved in: (i) capillary tube formation of human ECs using 3D collagen matrices [ 10 , 16 ]; (ii) the inflammatory response of ECs [ 17 ]; (iii) the atherosclerotic plaque vulnerability [ 18 20 ]; and (iv) the cross-talk between human airway basal cells and ECs [ 21 ]. Interestingly, MMP14 is upregulated in wound-derived blood vessels compared with vessels from intact human skin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%